Customers’ Preference of Palpali Dhaka Garments in Kathmandu Valley Ordered Logistic Model - Ghimire, Yogesh; Paudel, Udaya Raj; Basyal, Devid Kumar; Lawaju, Purnima; Bhandari, Anil (The Harvest, 2024)
Dhaka is a handcrafted cloth with a specific meaning in Nepal. Despite its indigenous value, Producer & Supplier are not aware in promotional activity of the Palpali Dhaka garment is not sufficient. So, there is lack in preference of Palpali Dhaka garment. Therefore, the aim of this study is to analyze the determinant of customer preference of Palpali Dhaka garment in Kathmandu valley. Following exploratory research design was adopted and data was collected using structured questionnaire. Where ordered logistic model was used for inferential analysis, both descriptive and inferential analysis was used. Respondent were sampled from Kathmandu valley. Simple random sampling technique was used for 196 respondents. KOBO toolbox was used for data collection. The study found that the promotion of Palpali Dhaka garment is affected by major determinants. The factors which are significant to customer preference of Palpali Dhaka garment are Brand, Quality, Knowledge source, Family type, Advertising, Reducing Challenges which shape customer preference. Based on the findings of the study, the study concluded that for the better promotion of Palpali Dhaka garment the producer and supplier should improve promotional activity, improve Brand and Quality of Palpali Dhaka.